Assessment of Fasting Blood Glucose in Chronic Periodontitis Patients Visiting a Tertiary Hospital - Dhakal, Robins; Sharma, Shivalal; Shrestha, Sajeev; Goel, Khushboo; Lamsal, Madhab; Singh, Ripu (Nepal Journal of Health Sciences, 2022)
Introduction: It is well-established that diabetes unfavorably influences periodontal health and results in periodontitis. However, upcoming evidence also shows that periodontitis initiates a chronic state of insulin resistance leading to hyperglycemia.Objectives: We designed this study to assess fasting blood glucose levels in chronic periodontitis patients and also explore the relationship between severity of chronic periodontitis and fasting blood glucose levels with an analysis of their risk factors in adult the population of eastern Nepal.Methods: A cross-sectional hospital-based study was conducted on a total of 141 chronic periodontitis patients aged 30-55 years who were divided into Group A (Mild periodontitis) and Group B (Moderate/ Severe periodontitis) according to the American Academy of Periodontology / Centres for Disease Control (AAP/ CDC) criteria. Fasting blood glucose level was analyzed as normal (